EFEKTIVITAS PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK (PMR) PADA PEMBELAJARAN MATEMATIKA SD - Ni Putu Datrini; Putu Sri Widiastini; I Made Sujana Adnyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify and understand the effectiveness of the Realistic Mathematics Education (RME) approach in mathematics learning at elementary schools. The RME approach brings mathematics closer to the students' environment, allowing students to understand mathematics more accurately. This study uses the Systematic Literature Review (SLR) method. Through the SLR method, data collection can be carried out systematically, structurally, and planned. Data collection is done by reviewing all articles related to mathematics education within the period of 2016 – 2026. The articles used in this study consist of 10 national journal articles obtained from Google Scholar. Based on this research, it is known that Realistic Mathematics Education (RME) is able to improve student learning outcomes and can enhance students' mathematical abilities. Through RME, mathematics learning in elementary schools tends to use contextual problems as a starting point for learning, allowing students to have mathematical problem-solving skills, develop critical thinking abilities, and increase student activity in the classroom